Dead to rights - Jance, Judith A., 1944- (Suspense / Harper, 2009)
A woman is cruelly cut down in a remote corner of Arizona, killed on her nineteenth wedding anniversary by a drunk motorist.A year later, the driver himself dies badly, and all suspicions point to the slain woman's still-grieving husband as his murderer.But the truth is rarely black and white in the long Southwestern shadows, and one law officer is not rushing to condemn the tragic widower so quickly:Joanna Brady, Sheriff of Cochise County.Brady's convictions, however, are leading her on a twisted trail through inhospitable country-and setting her on a path that will bring her face-to-face with cold, calculating death in the high, lonely desert